(untitled) (Proceedings of the International Conference on Education, 2021)
The pandemic’s historical challenge has forced the international academic community to design new learning strategies, explore teaching methods, and develop skills through digital education. Particularly in medical education, early hands-on training is vital for the development of clinical skills. Remote simulations pose an innovative opportunity to encourage reflection on performance and transfer knowledge towards a demonstrable experience. The objective of this study was to develop and assess a remote-synchronous simulation experience. The study considered a quantitative approach with a descriptive and cross-sectional design. The sample consisted of 54 fourth-year medical students enrolled in a distance course on respiratory pathophysiology. The strategy was implemented through remote-synchronous simulations of 90 minutes using a videoconference platform. Students experienced the images, sounds, voices, and tension of an emergency room setting. The process considered 3 phases: 1)Design 2) Implementation 3)Reflective moment. To assess the experience, students were asked to participate in a survey with a 5-point Likert scale, where 5 depicts a more favorable response. Results show that students believe adapting to the remote-simulation was easy (3.92), and participating in the innovation was satisfactory for them (4.70). This remote-synchronous simulation of an emergency room for medical students provided a significant learning experience and a space for reflection that was highly valued for students. It is essential to highlight that it was easy to implement for the faculty members, and it was a low-cost alternative to offer early training experience amid the pandemic. This model may be transferable for other contexts and professions to enrich training in blended-learning formats.